PENGARUH HARGA DAN PEMAKAIAN PERSEDIAAN BAHAN BAKU TERHADAP VOLUME PRODUKSI PADA PT. KELOLA MINA LAUT DI GRESIK - BAYU YRI WIDHARTO (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2018)
The purpose of the research was to know the affect of many factors which affected to the production volume in PT. Kelola Mina Laut Gresik. What the price of raw materials was and the used of raw materials partially and simultan eously affected on the production volume. The analysis tool which used was a model of multiple linear regression. Hypothesis testing used t test and F test, both at the significant level 5%. Based of the analysis of research on PT Kelola Mina Laut Gresik. Partially, inventory raw material price had not significant effect on the production volume, consumption of raw material inventory affected significantly of the production volume. Inventory of raw material price and the use of raw material simultan eously affect significantly to the production volume.